Manuscripts of the Old Javanese Baratayuda in the Merapi-Merbabu collection - Molen, Willem Van Der (Universiti Kebangsaan Malaysia, 2007)
This article studies three manuscripts of the old Javanese Baratayuda now kept in the Perpustakaan Nasional in Jakarta. One of them turns out to be a fragment that had separated from one of the others. These originated in Java, which raises the question about how they relate to the Javanese tradition of the Baratayuda. This tradition differed from the Balinese tradition, both in wording and metre. One of the manuscripts appears to be on a par with the Balinese tradition, while the second one reflects common Javanese practice in its metrical aspect but seems to by unique where the wording is concerned. In addition, the latter is a small-size reproduction of a selected passage of the text. The conclusion is that the so-called Merapi-Merbabu Collection to which both manuscripts belong adds a new dimension to the study of the tradition of Old Javanese literature